Effect of bottom front roller eccentricity on yarn unevenness (U%), mass variation (CV%), and hairiness in PV 30 ring spinning - Dedy Harianto; Mokh Afifuddin; Siti Aisyah; Hendri Pujianto; Ratna Rosita Pangestika (OPSI, 2026)
This study demonstrates that bottom front roller eccentricity in ring spinning negatively affects PV 30 yarn quality by increasing yarn unevenness (U%) and mass variation (CV%). Using a paired-sample experimental design and paired t-test analysis, the study evaluated yarn quality before and after corrective alignment of the bottom front roller under controlled mechanical and environmental conditions. Yarn unevenness decreased from 9.43 ± 0.20 to 8.55 ± 0.06, while yarn mass variation decreased from 11.87 ± 0.30 to 10.76 ± 0.10 after corrective alignment, indicating statistically significant improvements in drafting stability and yarn uniformity (p < 0.05) with a large practical effect size based on Cohen’s d analysis (Cohen’s d = 1.21). The bottom front roller was specifically investigated because it directly controls fiber movement within the drafting zone, where mechanical instability can generate irregular fiber tension and drafting waves. In contrast, no statistically significant effect on yarn hairiness was observed. From an industrial engineering perspective, the findings highlight the importance of preventive maintenance and precise roller alignment in reducing off-quality yarn production, minimizing material waste, and improving operational efficiency. Unlike previous studies that broadly examined drafting irregularities and machine vibration, this study specifically isolates the effect of bottom front roller eccentricity before and after corrective alignment under controlled operating conditions.